Incidence of cerebrovascular accident following head and neck free tissue transfer surgery. Issue 3 (March 2023) - Diana, G.; Donnelly, R.; Steele, P.; McCaul, J.; McMahon, J.; Subramaniam, S.
Abstract: The aim of this study was to determine the incidence of postoperative cerebrovascular accident (CVA) following head and neck free tissue transfer and to identify predictive risk factors. A retrospective audit was performed of patients who underwent head and neck reconstructive surgery at Queen Elizabeth University Hospital between 2009 and 2020. The patient records were analysed to identify those who developed CVA within 30 days after surgery. A total of 1109 patients underwent head and neck free tissue transfer surgery, including 1048 neck dissection procedures. Of these, 78.6% had one or more identified risk factors for perioperative stroke. Five patients (0.45%) developed postoperative CVA. The results showed that CVA correlated to patients with hypercholesterolemia ( P = 0.007). This study demonstrates the safety of free tissue transfer. Despite underlying co-morbidities and risk factors, the incidence of CVA is low following surgery and manipulation of the major vasculature of the neck.